2016
DOI: 10.1049/iet-cvi.2015.0273
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of informative regions of a face for facial expression recognition

Abstract: The aim of facial expression recognition (FER) algorithms is to extract discriminative features of a face. However, discriminative features for FER can only be obtained from the informative regions of a face. Also, each of the facial subregions have different impacts on different facial expressions. Local binary pattern (LBP) based FER techniques extract texture features from all the regions of a face, and subsequently the features are stacked sequentially. This process generates the correlated features among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…There are well-known binary features such as local binary pattern (LBP) [60], Binary Robust Invariant Scalable Keypoints (BRISK) [61], Binary Robust Independent Elementary Features (BRIEF) [62], and the Oriented FAST and Rotated BRIEF (ORB) [63]. Among them, the LBP is widely utilized in computer vision, because it is a computationally simple non-parametric texture descriptor and can handle monotonic illumination variations well in the textured images [29,60,64]. Therefore, we used Local Binary Pattern (LBP) feature [60].…”
Section: Datasets and Data Augmentationmentioning
confidence: 99%
“…There are well-known binary features such as local binary pattern (LBP) [60], Binary Robust Invariant Scalable Keypoints (BRISK) [61], Binary Robust Independent Elementary Features (BRIEF) [62], and the Oriented FAST and Rotated BRIEF (ORB) [63]. Among them, the LBP is widely utilized in computer vision, because it is a computationally simple non-parametric texture descriptor and can handle monotonic illumination variations well in the textured images [29,60,64]. Therefore, we used Local Binary Pattern (LBP) feature [60].…”
Section: Datasets and Data Augmentationmentioning
confidence: 99%
“…Kumar et al [14] proposed a framework depending on getting the instructive regions of a face image. In the feature extraction stage, LBP features were extracted and then Procrustes analysis was used to model the reference image.…”
Section: Literature Surveymentioning
confidence: 99%
“…Input space does not separate training set linearly, but in the case of the attribute space, the training set will be linearly separable. This is known as the "Kernel trick" Proposed by Shenetal [14][15].…”
Section: Support Vector Machine Classifiermentioning
confidence: 99%
“…The obtained features are then classified using Sparse representation classifier. S. Kumar et al, [27] have used Local Binary Pattern descriptor to extract discriminative features from informative regions of face and the extracted informative region will estimates the importance of sub regions using projection analysis of expressive images. It is found that the performance of the proposed method is better than the existing methods on JAFFE face database given in Table 7.…”
Section: Analysis With Jaffe Databasementioning
confidence: 99%